Mednarodno poslovanje – hitro spreminjajoče se okolje - Stare, Viktor (Trajnost, 2025)
We live in a rapidly developing society where information management is an important activity. We are witnessing the rapid development of goods and services, which has a strong impact on the changing wishes and expectations of customers. Companies are constantly acquiring fresh information about changes in the environment so that they can respond to them in a timely and appropriate manner. They must identify problems, develop solutions and offer them to the market accordingly. In modern times, their business orientation which leads to good results, is guided by a correct understanding of the role and importance of the sustainable development of society as a whole and the location of the company‘s social responsibility in the environment. Companies must, as a goal, set their own responsible place in the circular flow of the economy, as they must be aware that the world or the environment around the company is only one that needs to be protected or respected. The purpose of the paper is primarily to present the meaning and role of globalization, business operations in the international environment, and consequently to determine the connection between the role of the global world and the sustainable development of society as a whole. The article presents the importance of understanding the social responsibility of companies on the market, their loction in the circular flow of the economy, as well as the understanding of the company as a socially responsible entity.
Keywords: družbena odgovornost; globalizacija; krožni tok gospodarstva; trajnostni razvoj